Notifications and Awareness: A Field Study of Alert Usage and Preferences - Iqbal, Shamsi; Horvitz, Eric (Association for Computing Machinery, Inc., 2010)
Desktop notifications are designed to provide awareness of information while a user is attending to a primary task. Unfortunately the awareness can come with the price of disruption to the task at focus of attention. We review results of a field study on the use and perceived value of email notifications in the workplace. We recorded users’ interactions with software applications for two weeks and studied how notifications or their forced absence influenced users’ quest for awareness of new email arrival, as well as the impact of notifications on their overall task focus. Results showed that users view notifications as a mechanism to provide passive awareness rather than a trigger to switch tasks. Turing off notifications cause some users to self interrupt more to explicitly monitor email arrival, while others appear to be able to better focus on their tasks. Users acknowledge notifications as disruptive, yet opt for them because of their perceived value in providing awareness.
Yale University Department of Computer Science Technical Report number 561